PENGARUH KADAR GARAM TERHADAP KANDUNGAN HISTAMIN, VITAMIN B12 DAN NITROGEN BEBAS TERASI IKAN TERI (Stolephorus sp) - Romawati, Marita Dwi; Ma'ruf, Widodo Farid; Romadhon, Romadhon (Jurnal Pengolahan dan Bioteknologi Hasil Perikanan, 2014)
Terasi is a fish paste which is a solid condiment and spesific aromafrom fermented shrimp. Salt in making terasi is contributeto prevent the damage of product by microorganism. The purpose of this research was to determine the effect of different salt concentrationsfor the content of histamine, vitamin B12 and free nitrogen fromanchovy terasi (Stolephorus sp.).The material used in this researchwerefresh anchovy (Stolephorussp.) and salt. Theparameter tested in this reseacrh are organoleptic, moisture content, aw, pH, histamine, vitamine B12 and free nitrogen . The research method used was experimental field. Analysis data in this research used an analysis of variance (ANOVA).The results of the research showed, organoleptic value of terasi with salt concentrations 2%, 8,5%, 15%, is 7,64£m£7,90; 8,08£m£8,62 and 7,74£m£7,96respectively,it indicated safe for consumption. Terasi with 2% salt concentration of histamine contain 31,13 mg/100g, B12 vitamin 31,44 mg/kg and 1,78% free nitrogen. Terasi with the salt concentration of histamine contain 8,5%, 25,46mg/100g, B12 vitamine 35,81 mg/kg and 2.29% free nitrogen. Terasi with 15% salt concentration of histamine containing 22,85 mg/100g, B12 vitamine 36,18 mg/kg and 2,70% free nitrogen. Salt concentrationhas different effects on histamine and B12 vitaminecontent and hasnot influence free nitrogen.